San Martín, J., La nueva imagen de Husserl. Lecciones de Guanajato, Ed. Trotta, Madrid, 2015, 204 pp. ISBN 978-84-9879-591-2 - Godoy, Ernestina (2016)
Fil: Ernestina Godoy. Universidad Nacional de Córdoba; Argentina